2022
DOI: 10.1002/clc.23832
|View full text |Cite
|
Sign up to set email alerts
|

Decongestive treatment adjustments in heart failure patients remotely monitored with a multiparametric implantable defibrillators algorithm

Abstract: Aims: HeartLogic algorithm combines data from multiple implantable defibrillators (ICD)-based sensors to predict impending heart failure (HF) decompensation. A treatment protocol to manage algorithm alerts is not yet known, although decongestive treatment adjustments are the most frequent alert-triggered actions reported in clinical practice. We describe the implementation of HeartLogic for remote monitoring of HF patients, and we evaluate the approach to diuretic dosing and timing of the intervention in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Nevertheless, studies have shown that with one parameter alone there may be no significant improvement in outcomes (38, 39). Algorithms including multiple parameters may be more appropriate but have to be evaluated (40)(41)(42).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Nevertheless, studies have shown that with one parameter alone there may be no significant improvement in outcomes (38, 39). Algorithms including multiple parameters may be more appropriate but have to be evaluated (40)(41)(42).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…We would like to thank Dr Imamura for his interest in our paper and we have greatly appreciated his insights on the current perspective related to heart failure (HF) monitoring. In this reply, we would reply to his thoughts and clarify some aspects of our work 1 . First, it is not entirely true that 44% “were not associated with heart failure‐related events” as this number more correctly represents the number of alerts not followed‐up by the physicians.…”
mentioning
confidence: 96%
“…In this reply, we would reply to his thoughts and clarify some aspects of our work. 1 First, it is not entirely true that 44% “were not associated with heart failure‐related events” as this number more correctly represents the number of alerts not followed‐up by the physicians. These could have been false positives, as Dr Imamura correctly implies, nonactionable alerts (therapy changes or interventions already undertaken), or more simply true positives not properly followed by clinical response.…”
mentioning
confidence: 99%
“…Methodology to monitor impending heart failure decompensation is receiving great concern to improve clinical outcomes in patients with chronic heart failure. Guerra et al 1 demonstrated that decongestive treatment adjustments triggered by the alerts of HeartLogic algorithm, which combines clinical data from multiple implantable defibrillator‐based sensors, was safe and effective. Of note, the early decongestive treatment and the use of high dose of diuretics were associated with more favorable outcomes.…”
mentioning
confidence: 99%
“…Of 242 alerts, 105 (44%) were not associated with heart failure‐related events. 1 Could the authors explain the reasons for such a high false alarm? Some heart failure events might not be detected appropriately by this technology.…”
mentioning
confidence: 99%